Targeting Indoleamine Dioxygenase and Tryptophan Dioxygenase in Cancer Immunotherapy: Clinical Progress and Challenges - Peng X; Zhao Z; Liu L; Bai L; Tong R; Yang H; Zhong L (Dove Medical Press, 2022)
Xuerun Peng,1,* Zhipeng Zhao,1,* Liwen Liu,2 Lan Bai,1 Rongsheng Tong,1 Hao Yang,3 Lei Zhong1 1Department of Pharmacy, Personalized Drug Therapy Key Laboratory of Sichuan Province, Sichuan Provincial People's Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, Sichuan, 610072, People's Republic of China; 2Department of Obstetrics and Gynecology, Fengrun District People's Hospital, Tangshan, Hebei, 063000, People's Republic of China; 3POWERCHINA Chengdu Engineering Corporation Limited, Chengdu, Sichuan, 610072, People's Republic of China*These authors contributed equally to this workCorrespondence: Lei Zhong, Department of Pharmacy, Personalized Drug Therapy Key Laboratory of Sichuan Province, Sichuan Provincial People's Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, Sichuan, 610072, People's Republic of China, Email zhl7235301@163.com Hao Yang, POWERCHINA Chengdu Engineering Corporation Limited, Chengdu, 610072, Sichuan, People's Republic of China, Email yanghao@chidi.com.cnAbstract: Indoleamine 2.3-dioxygenases (IDO1/2) and tryptophan 2.3-dioxygenase (TDO) are the initial and rate-limiting enzymes in tryptophan metabolism, which play an essential role in mediating immunosuppression in tumor microenvironment. Accumulating evidence has indicated that both IDO1 and TDO are highly expressed in many malignant tumors, and their expression is generally associated with reduced tumor-infiltrating immune cells, increased regulatory T-cell infiltration, as well as cancer progression and poor prognosis for malignancies. A large number of IDO1 and TDO inhibitors have been screened or synthesized in the last two decades. Thus far, at least 12 antagonists targeting IDO1 and TDO have advanced to clinical trials. In this account, we conducted a comprehensive review of the development of IDO1 and TDO inhibitors in cancer immunotherapy, particularly their clinical research progress, and presented the current challenges and corresponding solutions.Keywords: indoleamine 2, 3-dioxygenase, tryptophan-2, 3-dioxygenase, tryptophan metabolism, cancer immunotherapy, immune tolerance